Hemoglobin Levels among Farmers: The Impact of Pesticide Exposure and Geographical Factors in Lotto Village, Ternate City - Irma B Hi Lewa; Aan Yulianingsih Anwar (Al-Hijrah Indonesia, 2026)
Farmers face substantial occupational risks from pesticide exposure during crop spraying, which can disrupt hematopoiesis and alter hemoglobin (Hb) levels, potentially inducing anemia or physiological polycythemia. This study assessed Hb profiles and associated occupational and environmental determinants among farmers in Loto Village, West Ternate City. A descriptive cross-sectional design was employed, involving 35 active farmers. Capillary Hb concentrations were quantified via Point-of-Care Testing (POCT), along with data on spraying frequency, work duration, compliance with personal protective equipment (PPE), gender, and residential altitude. Results revealed that 80% (n=28) maintained normal Hb levels, whereas 11% (n=4) had low Hb levels, and 9% (n=3) had elevated Hb levels. Reduced Hb was predominantly observed among female farmers and individuals who used incomplete PPE during chemical handling. Conversely, elevated Hb concentrations were concentrated among male farmers residing in high-altitude zones, indicating an adaptive erythropoietic response to hypobaric hypoxia. Frequent pesticide application (≥3 times/week) and extended occupational tenure (>5 years) further correlated with Hb variability. These findings indicate that while hematological homeostasis is largely preserved in this cohort, inadequate PPE compliance and female sex elevate anemia susceptibility, whereas high-altitude residence drives compensatory polycythemia. Routine hematological surveillance and enforced adherence to PPE are essential for mitigating pesticide-induced hematotoxicity and optimizing occupational health outcomes in agricultural populations.